Arabidopsis root apical meristem adaptation to an osmotic gradient condition: an integrated approach from cell expansion to gene expression - Píriz-Pezzutto, Selene; Martínez-Moré, Mauro; Sainz, María Martha; Borsani, Omar; Sotelo-Silveira, Mariana (Frontiers in Plant Science, 2024)
Climate change triggers abiotic stress, such as drought and high salinity, that can cause osmotic stress. Water availability can limit plant growth, and the root tip tissues initially sense it. Most experiments destined to understand root growth adaptation to osmotic stress apply homogeneous high osmotic potentials (osmotic shock) to shoots and roots. However, this treatment does not represent natural field conditions where a root may encounter increasing osmotic potentials while exploring the soil. Osmotic shock severely reduces root growth rate, decreasing cell division in the proximal meristem and reducing mature cell length. In this work, we developed an in vitro osmotic gradient experimental system with increasing osmotic potentials. The system generates a controlled osmotic gradient in the root growth zone while exposing the aerial tissues to control conditions. The osmotic gradient system allowed Arabidopsis seedlings of Col-0 and ttl1 mutant (affected in the gene TETRATRICOPEPTIDE THIOREDOXIN-LIKE 1 (TTL1)) to sustain proper root growth for 25 days, reaching osmotic potentials of -1.2 MPa. We demonstrated that roots of seedlings grown in the osmotic gradient sustain a higher root growth rate than those that were grown under a homogeneous high osmotic potential. Furthermore, we found out that the expression of some genes is modified in the roots grown in the osmotic gradient compared to those grown in osmotic shock. Our data indicate that using an osmotic gradient can improve our understanding of how plants respond to osmotic stress and help find new genes to improve plant field performance.